Congenital anomalies associated with hypothyroidism. Issue 6 (June 1986) - Bamforth, J S; Hughes, I; Lazarus, J; John, R
Abstract : Seven of the 34 infants identified through the Welsh Hypothyroid Screening Programme have additional congenital abnormalities. Two infants have a previously undescribed syndrome, two have chromosomal abnormalities, two have congenital heart disease, and one has a myelomeningocoele. Congenital hypothyroidism often seems to be associated with other congenital abnormalities.